Correlation between abdominal aortic calcification and peripheral blood lymphocyte subsets in patients with peritoneal dialysis - Ren Cai-xia; Han Kun; Liu Yuan; Xing Wen-xiu; Lu En-bang; Gong Xue; Wan Mei-yan (Linchuang shenzangbing zazhi)
Objective To explore the relationship between abdominal aortic calcification（AAC）and peripheral blood lymphocyte subsets in patients on peritoneal dialysis（PD）.Methods The clinical data of 86 patients on PD were collected.Abdominal lateral plain film was taken for determining the occurrence of AAC and abdominal aortic calcification（AAC）score was calculated.Based upon the AAC scores, they were divided into three groups of non/mild calcification（0≤AACs≤4,n=41）,moderate calcification（5≤AACs≤15,n=28）and severe calcification（16≤AACs≤24,n=17）.Flow cytometry was utilized for detecting lymphocyte subsets in peripheral blood.The percentage of CD3+,CD3+CD4+,CD3+CD8+,CD4+/CD8+,Treg, CD19+,CD16+CD56+ and CD8+DR+lymphocyte count and ratio of CD4+/CD8+were calculated.Spearman’s correlation analysis was performed for analyzing the correlation between AAC and peripheral blood lymphocyte subsets and clinical parameters.Logistic regression was employed for analyzing the risk factors of AAC in PD patients.Results Among three groups, statistically significant differences existed in age, diabetic nephropathy, chronic glomerulonephritis, albumin, blood phosphorus and alkaline phosphatase levels（P<0.05）.Spearman’s correlation analysis indicated that degree of AAC was positively correlated with patient age, dialysis age, parathyroid hormone, blood phosphorus, alkaline phosphatase, high-sensitivity C-reactive protein, CD4+/CD8+,CD16+CD56+ and CD8+DR+（r=0.352,0.284,0.226,0.299,0.265,0.285,0.236,0.228,0.292,P<0.05）and negatively correlated with albumin and Treg（r=-0.222,-0.354,P<0.05）.Logistic regression model results implied that age（OR=1.060,95%CI 1.008～1.116,P<0.05）,CD4+/CD8+（OR=25.441,95% CI1.561～414.659,P<0.05）and Treg（OR=0.427,95%CI 0.255～0.715,P<0.05）were independent risk factors for moderate-to-severe AAC in PD patients.Conclusion The degree of AAC in PD patients has a certain correlation with the changes of lymphocyte subsets in peripheral blood.Lower percentage of Treg cells and higher ratio of CD4+/CD8+accelerate the progression of AAC.The change of peripheral blood lymphocyte subsets of PD patients may provide a new direction for the prevention and treatment of AAC.